Exploring the social, ethical, legal, and responsibility dimensions of artificial intelligence for health – a new column in Intelligent Medicine - Achim Rosemann; Xinqing Zhang (Intelligent Medicine, 2022)
This essay is the starting point of a new column in Intelligent Medicine that invites interdisciplinary perspectives on the social, ethical, legal, and responsibility aspects of the use of artificial intelligence (AI) in medicine and health care. Papers in this column will examine the practical, conceptual, and policy dimensions of the use of AI for health-related purposes from comparative and international perspectives. We invite contributions from around the world in all application areas of AI for health, including health care, health research, drug development, health care system management, as well as public health and public health surveillance. The column aims to provide a forum for reflective and critical scholarship that contributes to the ongoing academic and policy debates about the development, use, governance, and implications of AI in medical and health care settings.To launch the column, we first provide an overview of recent approaches that have been developed to identify and address the effects and potential impacts of science and technology innovations on human societies and the environment. These include ethical, legal, and social implications/aspects (ELSI/A) research, responsible research and innovation (RRI), sustainability transitions research, and the use of international standard-setting instruments for responsible and open science issued by the United Nations Educational, Scientific, and Cultural Organization (UNESCO), the World Health Organization (WHO), and other international bodies. In Part Two of this essay, we discuss some of the central challenges that arise with regard to the integration of AI and big data analytics in medical and health care settings. This includes concerns regarding (i) the control, reliability, and trustworthiness of AI systems, (ii) privacy and surveillance, (iii) the impact of AI and automation on health care staff employment and the nature of clinical work, (iv) the effects of AI on health inequalities, justice, and access to medical care, and (v) challenges related to regulation and governance. We end the essay with a call for papers and a set of questions that could be relevant for future studies.